Excluir, isolar e conviver: um estudo sobre a lepra e a hanseníase no Brasil - Luciano Marcos Curi (2010)
Leprosy and hansen's disease are different. A! particularized historical examination evidences that assertion. Both of them belong to different times and situations and are linked to their own thought style . This work located leprosy and hansen's disease in their uniqueness, these views from the Brazilian history properly contextualized in Western history. In this context, it stresses the ruptures and peculiarities of both, in contrast withthe generally established continuity between them. It also seeks to show that the thoughtless use of the word leprosy eclipses socio-historical discontinuity that existed embodied in practices of exclusion and isolation of lepers. These practices have been widely used, but they were different and the variation that historically represented is incontestable evidence of discontinuities in the history of leprosy and the impropriety of bringing it to the history of current hansen's disease. Therefore, this research sought to show that hansen's disease is a new disease and not a new name for the old leprosy. Examined retrospectively, dodging routine anachronisms, the advent of hansen's disease became evident from the genesis and emergence of specific scientific knowledge that came to define this disease. This finding was possible after the realization of a culturalhistorical analysis undertaken under the inspiration of the theory of Ludwik Fleck. In short, definitely, hansen's disease is not leprosy.